Histoplasmosis masquerading as tongue carcinoma: a rare case report in an immunocompetent male - Aregala, Praneeth; Marda, Sachin; Gowda, Sreehari; Kelkeri, Manjula Vijayanand; Jyoshna, T. M. (International Surgery Journal, 2025)
Darling’s disease, another name for oral histoplasmosis, is an uncommon but important form of Histoplasma capsulatum infection that can appear as oral cavity lesions that frequently mimic cancers like squamous cell carcinoma. Immunocompromised people, notably those with HIV, are most vulnerable to this fungal infection, while immunocompetent patients can still get it. Because of their appearance and chronic nature, the clinical presentation usually consists of painful, ulcerative lesions that could be mistakenly diagnosed as cancer. In the uncommon instance described in this analysis, an 80-years-old man who had no known addictions or comorbidities showed up with a non-bleeding ulcero-proliferative lesion on his tongue that had been there for two months. The lesion was eventually determined to be oral histoplasmosis after being misdiagnosed as mouth cancer. The diagnostic difficulties associated with this illness were highlighted by the histopathological investigation, which showed granulomatous inflammation and the distinctive yeast forms of Histoplasma. Inappropriate treatment plans and delays in efficient management can result from misdiagnosis. This example emphasizes how crucial it is to take oral histoplasmosis into account when making a differential diagnosis for oral lesions, especially in areas where it is endemic. To get positive results and avoid consequences from misdiagnosis, early detection and adequate antifungal medication are essential.